Gender Differences in Self-Determined Motivation and Subjective Well-Being of Adapted Sport Athletes Members of the Special with Intellectual and Developmental Difficulties Members - Ana, Domingues (2021)
The Theory of Self-Determination has been used as a theoretical model of support in several studies on motivation in Sport. In this sense, we realize that motivation is a topic to which researchers have devoted much of their time, however, when researching adapted sports, and the person with Intellectual and Developmental Difficulty we observe a shortage in research.This study aimed to verify the levels of self- determination and subjective well-being of athletes members of the Special Olympics of Portugal, and ii) to compare the variables under analysis according to gender. In this quantitative study participated 94 athletes of Adapted Sports, aged between 11 and 63 years (‹=32.61 ± SD=13.8) of both genders, competitors of individual and collective sports.The monitoring instruments used were Behavioral Regulation in Sport Questionnaire (BRSQ), Basic Psychological Needs Exercise Scale (BPNES), Life Satisfaction Scale (S WLS) and Positive and Negative Attachment Scale (PANAS). Data analysis was based on the verification of the internal consistency of the scales applied through the calculation of alpha and Cronbach, descriptive analysis of data and application for gender comparison through the nonparametric test U Mann- Whitney, as well as a linear regression, meeting a significance level of 0.05. As a result, we observed that the satisfaction of basic psychological needs and motivation predict good levels of life satisfaction also of positive attachment.We also found statistically significant differences in life satisfaction and negative attachments when comparing gender outcomes.